APLIKASI TEKNOLOGI PENGOLAHAN AIR ASIN DESA TARUPA KECAMATAN TAKA BONERATE KABUPATEN SELAYAR - Widayat, Wahyu (Jurnal Air Indonesia, 2007)
Takabonerate is one of the 23 regencies in South Sulawesi where it is locates at the southern parth of South Sulawesi Province and it is surrounded by flores sea. As maritime regency, its mainland is 1,188.28 km2 (5.23%) and the sea is approximately 21,138.41 km2 (94.68%). It has 126 islands wich consist of small and big islands. Tarupa village’s a subdistrict located in a tidy and peat area. The community living in tarupa use surface water of river as the main clean water resource. The surface water is influenced by the tide of sea water. The surface water taste is very salty (TDS>12000ppm). The use of rain water as the second alternative is very limited, i.e it is only in rainy season. To deal with the chronic problem, such as the lack of clean water supply, it needs an appropriate water treatment technology. The suitable water treatment system is a combination of conventional and advanced technology. Desalination, such as Reverse Osmosis must be involved to reduce salinity of the raw water. A complete process includes the pretreatment and advance treatment. The pretreatment are oxidation and some common filtrations. The advance treatment is a molecular filtration using a membran which the principal is reverse osmosis pressure. If the pilot water treatment plant is avalaible in Tarupa in Takabonerate, the clean water supply will not be a serious problem. Generally, it can also play an important role to increase the social level of community in South Sulawesi.. Kata Kunci : Teknologi, pengolahan, air asin, reverse osmosis, air minum.